TEACHERS’ PERCEPTIONS TOWARDS TEACHING WRITING USING WORD GAMES; THE CASE STUDY OF JUNIOR HIGH SCHOOLS IN SEMARANG, CENTRAL JAVA, INDONESIA - Dias Andris Susanto; Maria Yosephine (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2017)
This was a descriptive qualitative study which was done in 2017 at junior high schools in Semarang Central Java, Indonesia. This study focused on the teachers’ perception and teaching writing using word games. According to Chastain (1988) "writing is a basic communication skill and a unique tool in the process of second language learning" (p.244). The problem of this study was what are the teachers’ perception towards the word games used in enhancing the students’ writing skill? The sample of the research were 6 junior high schools’ students in Semarang central java, Indonesia. They were students of grade eighth at SMP N 8, SMPN 39, SMPN 36, SMP Institut Indonesia, SMP PGRI Semarang, and SMP Theresiana Semarang. A structured interview was kindly used as the instrument in collecting the data. The findings are; 1) Teaching writing is not easy and need to be creative to make students understand since they have to master the way hoe to organize a good paragraph or text. 2) Usually they do not apply any games in teaching writing since they got the material for granted. 3) Most of the teachers have known what word game is. Even they have applied it sometimes in speaking and vocabulary. 4) Teachers rarely do teaching English using word games by purpose. Especially teaching writing, teachers do not really pay attention on the current skill. 5) Even though some teachers do not really understand the way to use word games in the case of implementation but then, they are aware that students need a motivation in a space of teaching and learning process during filling the material. 6) Teachers like teaching writing using word games because word games can help them to motivate students in following the questions since the love playing while learning in the classroom. 7) teachers can motivate students to follow the lesson with fun, teachers easily follow the word games because it is equipped by the clear instructions, there are various word games which are related to teaching skills, word games are easily made/created by teachers based on the need of the lesson plan, word games are the simplest media to teach and long life. 8) word games which applicable to teach writing using word games are entitled broken sentence, mixed story, arranging sentence in a story, and getting occupation. The conclusions are The teachers’ perceptions towards teaching writing using word games are; teachers feel happy and fun during teaching writing using word games, teachers need more energy and time to maintain the word games, teachers should focus on the goal of writing mastery not the game itself, teachers should be creative in creating and organizing the word games, and teachers believe that word games are able to motivate students in following the lesson.  Key words: teachers’ perception, teaching writing, word games